The effect of introducing various genes for rust resistance by back crossing, on the yield and quality of the wheat cultivars Flameks and Skemer - Horsten, Machteld B (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 1979.